The role of imaging and sentinel lymph node biopsy in patients with T3b-T4b melanoma with clinically negative disease - Papageorge, Marianna V.; Maina, Renee M.; King, Amber Loren O.; Lee, Victor; Baumann, Raymond; Pucar, Darko; Ariyan, Stephan; Khan, Sajid A.; Weiss, Sarah A.; Clune, James; Olino, Kelly (Frontiers in Oncology, 2023)
Background: Previous studies demonstrate minimal utility of pre-operative imaging for low-risk melanoma; however, imaging may be more critical for patients with high-risk disease. Our study evaluates the impact of peri-operative cross-sectional imaging in patients with T3b-T4b melanoma. Methods: Patients with T3b-T4b melanoma who underwent wide local excision were identified from a single institution (1/1/2005 – 12/31/2020). Cross-sectional imaging was defined as body CT, PET and/or MRI in the perioperative period, with the following findings: in-transit or nodal disease, metastatic disease, incidental cancer, or other. Propensity scores were created for the odds of undergoing pre-operative imaging. Recurrence free survival was analyzed using the Kaplan-Meier method and log-rank test. Results: A total of 209 patients were identified with a median age of 65 (IQR 54-76), of which the majority were male (65.1%), with nodular melanoma (39.7%) and T4b disease (47.9%). Overall, 55.0% underwent pre-operative imaging. There were no differences in imaging findings between the pre- and post-operative cohorts. After propensity-score matching, there was no difference in recurrence free survival. Sentinel node biopsy was performed in 77.5% patients, with 47.5% resulting in a positive result. Conclusions: Pre-operative cross-sectional imaging does not impact the management of patients with high-risk melanoma. Careful consideration of imaging use is critical in the management of these patients and highlights the importance of sentinel node biopsy for stratification and decision making.